Curriculum of the electrical mechanical engineering degree and the specific skills demanded by the Peruvian labor market - Romero-Carrión, Violeta (2024)
The correlation between the curriculum of the Electrical Mechanical Engineering degree at the National University of Engineering (UNI), Lima, Peru and the specific skills demanded by the Peruvian labor market is presented. For this case study, a methodology with a quantitative approach, transversal type, non-experimental design and correlational level was considered, applying a survey to a sample of five professors from the Faculty of Mechanical Engineering of the UNI, by profession a Mechanical Engineer, Electrician and 25 graduates of said career. The questionnaires evaluated the curriculum of the aforementioned career, in force since 2020, and the specific skills (technical skills) demanded by the Peruvian labor market. In addition, Spearman's Rho hypothesis test was applied, obtaining as a result: (rS = 0.53; p = 0.003). It is concluded that there is a significant level, with a moderate correlation, between the curriculum of the Electrical Mechanical Engineering degree at UNI and the specific skills demanded by the Peruvian labor market. According to the aforementioned, periodic updating is recommended of the study curriculum.